Discrimination Against the Internally Migrated Female Workers: A Study on Dhaka City (Social Science Review, 2023)
The specific focus of this study is on the female workers of Dhaka city who are migrated from different parts of the country. It aims to explore how internally migrated female workers are subjected to discrimination in their workplaces.In this regard, the study has analysed the perceptions of internally migrated female workers employed in different sectors. The data collection methods include survey, KII, FGD and observation. The findings of this study show that more than one-fourth (29.17%) of the female workers perceive being discriminated in their workplaces. Sexual identity is found to be the key ground of discrimination. Discriminatory work environment prevails in almost all the sectors migrated female workers are employed in. The major types of discrimination identified by this study include genderbased disparity in payment, unfavourable work environment for women due to sexual harassment, invidious selection in hiring and promotion, and denial of rights during pregnancy. Though these forms of discrimination prevail across occupations, there are discrepancies in this regard. Domestic workers report the highest extent of pregnancy-related discrimination, but they emphasized oncomparatively lower extent of gender-based payment disparity. Garment workers report a very low level of sexual harassment but a higher level of pay disparity. Payment disparity is a common concern identified across the occupations covered in this study.Social Science Review, Vol. 38(2), December 2021 Page 135-157